2000
DOI: 10.1002/1521-3773(20000818)39:16<2934::aid-anie2934>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

DeNOx of Exhaust Gas from Lean-Burn Engines through Reversible Adsorption of N2O3 in Alkali Metal Cation Exchanged Faujasite-Type Zeolites

Abstract: NO and NO2 associated as the asymmetric N2O3 conformer compete with water molecules for coordination with sodium cations of the sodium–water clusters in supercages of the Na‐Y zeolite. This reactive NOx adsorption is reversible (see picture), not sensitive to SO2, and presents an alternative method for the removal of NOx from lean‐burn exhaust gas without the formation of surface nitrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 16 publications
3
37
0
1
Order By: Relevance
“…Neutron‐ and X‐ray‐diffraction techniques revealed the presence of guest molecules interacting with the sodium ions, which results in a reorganization of the cation distribution 1a. 3a,3b The presence of water molecules in the structure has a strong impact on position and occupation numbers of sodium atoms 5. 4a,b,c Exposure of Na–Y zeolite to a gas mixture containing 5–10 % water at 250 °C results in a water content of 50–60 water molecules per unit cell 5.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neutron‐ and X‐ray‐diffraction techniques revealed the presence of guest molecules interacting with the sodium ions, which results in a reorganization of the cation distribution 1a. 3a,3b The presence of water molecules in the structure has a strong impact on position and occupation numbers of sodium atoms 5. 4a,b,c Exposure of Na–Y zeolite to a gas mixture containing 5–10 % water at 250 °C results in a water content of 50–60 water molecules per unit cell 5.…”
mentioning
confidence: 99%
“…3a,3b The presence of water molecules in the structure has a strong impact on position and occupation numbers of sodium atoms 5. 4a,b,c Exposure of Na–Y zeolite to a gas mixture containing 5–10 % water at 250 °C results in a water content of 50–60 water molecules per unit cell 5. These water molecules interact with the sodium ions of the host to form a complex water–cation structure.…”
mentioning
confidence: 99%
“…However, addition of a controlled amount of water forces the radicals to depart into the alkane liquid surrounding the zeolite crystal, and this allows to start alkane autoxidation at clearly lower temperatures than in an uncatalyzed process [36]. Another unexpected observation was that Na-Y zeolite is an excellent adsorbent for NO x [37,38]. NO x can be trapped as an N 2 O 3 molecule in the faujasite cages, at a specific location in the network of sodium ions and water molecules (Fig.…”
Section: Redox Catalysis With Transition Metal Ion Exchanged Faujasitesmentioning
confidence: 84%
“…Potential NO x adsorbents include transition metal oxides, [10] hydrotalcite-like compounds, [11,12] perovskites, [13,14] activatied carbon, [15] α-FeOOH dispersed on activated carbon fibers, [16,17] Pt-Ba/γ-Al 2 O 3 [18] and Pt/K/γ-Al 2 O 3 [19] . [24] And the NO x adsorption capacity for metal ion-exchanged Y-type zeolites decreased in the order of Ba-Y>Cs-Y>Na-Y>Li-Y. [20][21][22][23][24][25][26][27] Iwamoto et al [22] prepared a series of metal ion-exchanged ZSM-5 zeolites, and found that copper ion-exchanged ZSM-5 zeolites showed great ability for reversible adsorption of NO at 273 K. Kröcher et al [23] discovered adsorption capacity for NO 2 was stronger than that for NO adsorption on Cu-ZSM-5 zeolites and the presence of water in the feed decreased its adsorption capacity for NO 2 .…”
Section: Introductionmentioning
confidence: 99%